2012
DOI: 10.2320/jinstmet.76.422
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Surface Hardness of S45C Steel by AIH-FPP/Gaseous Nitriding Treatment

Abstract: In this study, in order to increase surface hardness of S45C steel, hybrid surface modification treatment which is a combination of atmospheric controlled induction heating fine particle peening (AIH FPP) and gaseous nitriding, were developed. Surface microstructures of gaseous nitrided specimens pre treated with AIH FPP were characterized by a scanning electron microscope (SEM), an energy dispersive X ray spectrometer (EDX), X ray diffraction analysis (XRD) and X ray photoelectron spectroscopy (XPS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…1113) The authors have reported 11,12) that the local chromium concentration surrounding the porous region in the compound layer is high. Hosmani et al 13) reported that pores in the compound layer are formed due to recombination of nitrogen atoms to N 2 during the transformation of the ferrite matrix into iron nitrides surrounding CrN precipitates.…”
Section: Discussionmentioning
confidence: 99%
“…1113) The authors have reported 11,12) that the local chromium concentration surrounding the porous region in the compound layer is high. Hosmani et al 13) reported that pores in the compound layer are formed due to recombination of nitrogen atoms to N 2 during the transformation of the ferrite matrix into iron nitrides surrounding CrN precipitates.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that the thickness of the Cr diffused layer increases with the peening time and heating time during AIH-FPP treatment. 1,4,7,8) Therefore, we attempted to form thicker Cr diffused layers by doubling the peening time and heating time (peening time 60 s, heating time 120 s) during AIH-FPP treatment. Figure 8 shows the results of EDX analysis at the longitudinal section of the specimen subjected to AIH-FPP treatment under above conditions.…”
Section: Evaluation Of the Dlc Film Adhesion To Substrate By Indentatmentioning
confidence: 99%
“…46) It was also reported that when nitriding is applied to steels with a Cr diffused layer, the nitrided layer formed had higher hardness. 7,8) The use of particles that are highly reactive with the substrate has recently been determined to form intermetallic compounds composed of the elements of the shot particles and substrate on the treated surface. 913) In this research, we attempted to use AIH-FPP treatment as a pretreatment for coating of a carbon-based hard thin film of diamond-like carbon (DLC).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we conducted a study on the improvement effect and a series of experiments attempting to elucidate the mechanism underlining the effect of atmospheric-controlled induction heating and ne particle peening (AIH-FPP) [18][19][20][21][22][23][24][25] . For example, it was previously reported that by performing AIH-FPP on carbon steel using Cr particles, the components of the Cr particles were transferred onto the surface to be processed and diffused inside the substrate to form a Cr diffusion layer, whereby the corrosion resistance of the carbon steel was improved 22) .…”
Section: Introductionmentioning
confidence: 99%